Team Cohesion and Group Conflict in Brazilian Youth Athletes: Study Based on Achievement Goals Theory - Gabriel Lucas Morais Freire; Nayara Malheiros Caruzzo; Lenamar Fiorese; Sherdson Emanoel da Silva Xavier; Daniel Vicentini de Oliveira; José Roberto Andrade do Nascimento Junior (Desafio Singular, 2022)
The present study investigated the cohesion of teams and group conflict, based on the theory of compliance goals, in young Brazilian athletes participating in the final phase of the School Games in the state of Pernambuco. The participants were 413 young athletes, boys (n = 227) and girls (n = 186) aged between 14 and 17 years. Participants completed self-report questionnaires to assess the Youth Sport Environment Questionnaire (P-YSEQ), Group Conflict Questionnaire (P-GCQ) and Task and Ego Orientation in Sport Questionnaire (TEOSQ). The data were analyzed using hierarchical and non-hierarchical cluster analysis, chi-square test, multiple regression and multivariate variance analysis (MANOVA). The results showed that task orientation made the largest positive contribution to both task (β = .50, p < .001) and social (β = .31, p < .05) cohesion. Ego orientation made the largest positive contribution to task conflict (β = .49, p < .001) and social conflict (β = .67, p < .001), whilst task orientation made negative contribution (β = -.34, p < .05) for social conflict. Compared to the high task and low ego cluster (Cluster 3) was compared with low ego and task (Cluster 2) and high task and low ego cluster (Cluster 1), there was a significant difference between groups in task cohesion (p=.001), task conflict (p=.003) and social conflict (p=.001). It is concluded that task orientation seems to be a positive predictor of team cohesion, while ego orientation might predict positively group conflict and negatively task cohesion.